Persistence and Microevolution of Pseudomonas aeruginosa in the Cystic Fibrosis Lung: A Single-Patient Longitudinal Genomic Study - Bianconi, Irene; D’Arcangelo, Silvia; Esposito, Alfonso; Benedet, Mattia; Piffer, Elena; Dinnella, Grazia; Gualdi, Paola; Schinella, Michele; Baldo, Ermanno; Donati, Claudio; Jousson, Olivier (Frontiers in Microbiology, 2019)
Background During its persistence in cystic fibrosis (CF) airways, P. aeruginosa develops a series of phenotypic changes by the accumulation of pathoadaptive mutations. A better understanding of the role of these mutations in the adaptive process, with particular reference to the development of multidrug resistance (MDR), is essential for future development of novel therapeutic approaches, including the identification of new drug targets and the implementation of more efficient antibiotic therapy. Although several whole-genome sequencing studies on P. aeruginosa CF lineages have been published, the evolutionary trajectories in relation to the development of antimicrobial resistance remain mostly unexplored to date. In this study, we monitored the adaptive changes of P. aeruginosa during its microevolution in the CF airways to provide an innovative, genome-wide picture of mutations and persistent phenotypes and to point out potential novel mechanisms allowing survival in CF patients under antibiotic therapy. Results We obtained whole genome sequences of 40 P. aeruginosa clinical CF strains isolated at Trentino Regional Support CF Centre (Rovereto, Italy) from a single CF patient over an 8-year period (2007-2014). Genotypic analysis of the P. aeruginosa isolates revealed a clonal population dominated by the Sequence Type 390 and three closely related variants, indicating that all members of the population likely belong to the same clonal lineage and evolved from a common ancestor. While the majority of early isolates were susceptible to most antibiotics tested, over time resistant phenotypes increased in the persistent population. Genomic analyses of the population indicated a correlation between the evolution of antibiotic resistance profiles and phylogenetic relationships, and a number of putative pathoadaptive variations were identified. Conclusions This study provides valuable insights into the within-host adaptation and microevolution of P. aeruginosa in the CF lung and revealed the emergence of an MDR phenotype over time, which could not be comprehensively explained by the variations found in known resistance genes. Further investigations on uncharacterized variations disclosed in this study should help to increase our understanding of the development of MDR phenotype and the poor outcome of antibiotic therapies in many CF patients.